Design Of Accounting Information System for Transaction Management and Financial Reports at the Medan Pratama Haji Clinic - Daeli, Cosmas Samuel; Lumbanbatu, Maristella J.; Naibaho, Anggi Wulandari (Pascal: Journal of Computer Science and Informatics, 2025)
The rapid development of information technology requires healthcare institutions to digitize their financial data management to make administrative processes more effective and accurate. Medan's Pratama Haji Clinic currently still uses a manual system for recording transactions and preparing financial reports, resulting in frequent reporting delays, recording errors, and difficulties in tracking historical data. Based on these conditions, this study formulates three main problems, namely: how is the manual accounting information system currently implemented at Medan's Pratama Haji Clinic, what are the obstacles faced in managing financial reports manually, and how to design an accounting information system for managing transactions and financial reports. The purpose of this study is to design and build a computer-based accounting information system that can assist the process of recording transactions and preparing financial reports effectively at Medan's Pratama Haji Clinic. The research method uses the System Development Life Cycle (SDLC) with stages of analysis, design, implementation, and testing. Data were obtained through observation, interviews, and documentation. The system was designed using PHP and MySQL with the help of DFD, ERD, and Context Diagram tools. The results show that the system built is able to integrate all financial transaction processes and produce reports automatically, accurately, and efficiently. This system also facilitates management's oversight and decision-making. The study concluded that a computer-based accounting information system can replace manual systems and improve the efficiency of the clinic's finance department. A recommendation for further research is to develop this system with a web-based automated reporting module to make financial information more transparent and accessible.